An asteroseismic view of the radius valley: stripped cores, not born rocky - Van Eylen, Vincent; Lundkvist, Mia S. (Arxiv, 2018)
Various theoretical models treating the effect of stellar irradiation on planetary envelopes predict the presence of a radius valley: i.e. a bimodal distribution of planet radii, with super-Earths and sub-Neptune planets separated by a valley at around $≈ 2~R_\oplus$. Such a valley was observed recently, owing to an improvement in the precision of stellar, and therefore planetary radii. Here we investigate the presence, location and shape of such a valley using a small sample with highly accurate stellar parameters determined from asteroseismology, which includes 117 planets with a median uncertainty on the radius of 3.3%. We detect a clear bimodal distribution, with super-Earths ($≈ 1.5~R_\oplus$) and sub-Neptunes ($≈ 2.5~R_\oplus$) separated by a deficiency around $2~R_\oplus$. We furthermore characterize the slope of the valley as a power law \propto P^γ$ with $γ = {-0.09^{+0.02}_{-0.04}}$. A negative slope is consistent with models of photo-evaporation, but not with the late formation of rocky planets in a gas-poor environment, which would lead to a slope of opposite sign. The exact location of the gap further points to planet cores consisting of a significant fraction of rocky material.
Gesehen am 29.01.2019